2020
DOI: 10.33590/emjdiabet/20-00062
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Approaches in Immunotherapy for the Treatment of Type 1 Diabetes Mellitus

Abstract: The cure for Type 1 diabetes mellitus (T1DM) is likely to require an effective strategy for suppressing or evading the immune system. When considering curative treatments, it is almost inevitable to consider novel ways of inducing tolerogenicity to insulin-producing β cells. While the main mechanism of achieving tolerogenicity is restoring regulatory T cell (CD4+CD25+Fox3+) to effector T-cell (CD4+Fox3-) homeostasis, the means of achieving this are multifarious. The advent of a glucocorticoid-free immunosuppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Recent advances in metabolomics, transgenic mice and immunometabolism have shown that metabolic adaptation plays a crucial role in shaping T cell responses (12)(13)(14). T cell activation is linked to metabolic reprogramming to meet the increased energy and biomass demand (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in metabolomics, transgenic mice and immunometabolism have shown that metabolic adaptation plays a crucial role in shaping T cell responses (12)(13)(14). T cell activation is linked to metabolic reprogramming to meet the increased energy and biomass demand (15,16).…”
Section: Introductionmentioning
confidence: 99%